Undoing ruination in Jakarta : the gendered remaking of life on a wasted landscape - Tilley, Lisa; Elias, Juanita; Rethel, Lena (International Feminist Journal of Politics, 2017)
This intervention shares images and stories from the women evictees in Jakarta who collectively give voice to the psychic, physical, and material injuries inflicted by state dispossession in the city. Engaging Ann Laura Stoler’s (2013) language to expose the politics of ruination and preservation, we illustrate the gendered nature of the remaking of life on the most wasted of urban landscapes. The focus of this piece is Kampung Akuarium, a neighborhood violently evicted in April 2016 as part of a broader evictions regime in Jakarta under the governorship of Basuki Tjahaja Purnama, popularly known as Ahok. In the aftermath, Kampung Akuarium became the most restive of Jakarta’s landscapes as residents returned to make claims for justice and compensation, and to remake their lives directly on the rubble of their old homes in defiance of the city government. Flanked by the preserved warehouses of the VOC, the ruined neighbourhood ultimately became a site where colonial histories, state- and capital-inflicted expropriation and ruination, and gendered forms of injury and struggle all found material modes of expression alongside one another.